Graftbusters kontra kurakot (Philippine Center for Investigative Journalism, 2002)
Graftbusters dispels that notion and investigates what people are doing to fight graf and corruption from the citizens of Abra watching over public funds meant for roads and bridges, Makati businessmen fighting extortion by corrupt tax agents to born again Christian government employees who have taken up the cause of cleansing the corrupt Philippine bureaucracy.